2010
DOI: 10.1103/physreva.81.032502
|View full text |Cite
|
Sign up to set email alerts
|

Casimir piston of real materials and its application to multilayer models

Abstract: In this article, we derive the formula for the Casimir force acting on a piston made of real material moving inside a perfectly conducting rectangular box. It is shown that by taking suitable limits, one recovers the formula for the Casimir force acting on a perfectly conducting piston or an infinitely permeable piston. The Lifshitz formula for finite temperature Casimir force acting on parallel plates made of real materials is re-derived by considering the five-layer model in the context of the piston approac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…This result then coincides with the corresponding result derived in Ref. 1 whereas the results obtained in Refs. 2 and 3 correspond to plates with R q L(R) = −1 and R q L(R) = 1, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…This result then coincides with the corresponding result derived in Ref. 1 whereas the results obtained in Refs. 2 and 3 correspond to plates with R q L(R) = −1 and R q L(R) = 1, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…One can check that in the absence of amplification, our expression (30) tends to a known result for lossy media [2,64]. In the limit where the two perfect conductors are brought to infinity (i.e., d 1 , d 3 → ∞), Eq.…”
Section: Casimir Forces In Amplifying Multilayer Magnetodielectricmentioning
confidence: 60%
“…He demonstrated that in the case of a massless scalar field with Dirichlet boundary conditions, a finite attractive Casimir force without the surface divergence is obtained due to the cancelation of the divergent part of the Casimir force acting in the two regions separated by the piston. This result leads to a surge in the studying of the Casimir force on pistons with various geometric configurations and boundary conditions [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] . Casimir force on a rectangular piston in the spacetime with extra compactified dimensions has also been studied [88][89][90][91][92][93] .…”
Section: Casimir Piston Associated With Massless Fractional Klein-gormentioning
confidence: 99%
“…For Casimir effect on an n-dimensional (n = 1, 2 or 3) rectangular piston with mixed boundary conditions, namely with one surface having Dirichlet condition, and the other with Neumann condition, the resulting force is repulsive. 78 Other possible ways of obtaining a repulsive Casimir force have also been discussed 79,83,85,86,92,96 . In particular, the Casimir force of fractional Klein-Gordon field acting on a piston with fractional boundary conditions can be repulsive 85,96 .…”
Section: Casimir Piston Associated With Massless Fractional Klein-gormentioning
confidence: 99%